(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Background:Epilepsy is the second most common chronic neurological condition. Epilepsy means a tendency to have seizures i.e. recurrent unprovoked seizures. A seizure is a clinical events caused by an abnormal electrical discharge in brain (or) a transient disturbance of cerebral function due to an abnormal paroxysmal neuronal discharge in brain.Aims and Objectives: The main aim of the study is drug utilization evaluation of antiepileptic drugs among patients of different age groups in jayabharath hospital,Andhra Pradesh,. To assess drug utilization pattern of anti-epileptic drugs. METHODOLOGY:A prospective observational questionnaire based cross sectional study in 300 patients of various departments receiving atleastone AEDs. The subjects were included in the study only after they met the criteria for the study and after properly filling a informed consent form. The data was obtained by a questionnaire format and it is evaluated for utilization patterns, medication adherence. The cost of AEDs were calculated to evaluate total costs on each drug.RESULTS:Out of 300 patients, 210 were male and 90 were female. The age group 11- 20 years were found prominent with epilepsy. The average number of AEDs per patient was found to be 1.54. Among all the drugs prescribed phenytoin was the most common drug prescribed 223 (47.89%) for the treatment, followed by lorazepam 89 (19.09 %) and sodium valproate 40 (8.73 %). CONCLUSION:The use of AEDs was almost found to be rational. In this hospital the most commonly prescribed AEDs was phenytoin followed by lorazepam and in combinational therapy it was phenytoin + lorazepam. The utilization of drugs was obtained from the patients using questionnaire format and they showed high utilization of drugs.